GAIN ENHANCEMENT OF COMPACT ULTRA WIDEBAND ANTENNA - Mr. Bipin Bansode; Prof. Ramesh S. Pawase (International Journal of Innovations in Engineering Research and Technology, 2021)
A trend of portable device integration has arisen in last decade, due to the massive growth of wireless communications, and products are expected to have multiple wireless services with increased gain. As a result, a single, small antenna with the ability to operate effectively over broadband with near optimum gain is desired. Antenna is always designed upon the experience of the designer, which is an onerous and time-consuming work. Some parameters of the antenna, such as gain and S-parameter of monopole antenna, are not simple to control, which leads great difficulty for the designer to modify the structure for proper working conditions. A method is presented which is aimed at increasing the gain of ultra-wide band (UWB) antenna using the Grid SearchAlgorithm (GSA) without the need to increase its size. The antenna is analyzed by using the Method of moment (MoM) to achieve an ultra wide bandwidth characteristic and a maximum possible gain. The antenna has compact physical structure (30 mm × 33 mm.) and is designed on standard FR4 substrate of 1.6mm with anoperating frequency of 6.85 GHz. The simulated frequency response shows an excellent impedance bandwidth of 7.9 GHz or 115.3% over 3.1 to 11GHz for VSWR less than 2. The radiation patterns, peak gain, return loss & VSWR are presented and compared.